Transformations for climate change mitigation: A systematic review of terminology, concepts, and characteristics. (22nd September 2021) - Moore, Brendan; Verfuerth, Caroline; Minas, Angela Mae; Tipping, Christianne; Mander, Sarah; Lorenzoni, Irene; Hoolohan, Claire; Jordan, Andrew J.; Whitmarsh, Lorraine
Abstract: Deep, broad, and rapid society‐wide changes are urgently required to limit global temperature rise in line with the goals of the Paris Agreement. Since 2005, academics and policy makers have increasingly referred to such changes as transformations . This recent uptake and rapid diffusion of transformation‐related concepts in research on climate change mitigation calls for a systematic and up‐to‐date analysis. In this article, we address this gap by undertaking a systematic review of articles that use transformation‐related terms in the social science literature on climate change mitigation. Drawing on a corpus of 198 articles identified from Scopus, we find a diverse, fragmented research field that strongly focuses on the national, city, and international levels, the energy sector, and high‐income countries. Although the use of transformation terminology has increased rapidly, there are few shared definitions, which arguably constitutes a serious challenge to scholarship and evidence‐based policy making. To facilitate a more cumulative and impactful approach to research, we propose transformational climate change mitigation as a new umbrella term for the varied mitigation‐related societal transformations required to meet the goals of the Paris Agreement. We conclude by identifying priorities for future research. This article is categorized under: The Carbon Economy and Climate Mitigation > Benefits of Mitigation Abstract : Use of transformation‐related terms and concepts is increasing rapidly in the academic literature and among policy makers, but fragmentation and a lack of clear, shared definitions demands greater synthesis and further research.